ACK1 promotes gastric cancer epithelial–mesenchymal transition and metastasis through AKT–POU2F1–ECD signalling. Issue 2 (9th March 2015) - Xu, Song‐Hui; Huang, Jin‐Zhou; Xu, Man‐Li; Yu, Guangchuang; Yin, Xing‐Feng; Chen, De; Yan, Guang‐Rong
Abstract Amplification of the activated Cdc42‐associated kinase 1 (ACK1) gene is frequent in gastric cancer (GC). However, little is known about the clinical roles and molecular mechanisms of ACK1 abnormalities in GC. Here, we found that the ACK1 protein level and ACK1 phosphorylation at Tyr 284 were frequently elevated in GC and associated with poor patient survival. Ectopic ACK1 expression in GC cells induced epithelial–mesenchymal transition (EMT) and promoted migration and invasion in vitro, and metastasis in vivo; the depletion of ACK1 induced the opposite effects. We utilized SILAC quantitative proteomics to discover that the level of the cell cycle‐related protein ecdysoneless homologue (ECD) was markedly altered by ACK1. Overexpression of ECD promoted EMT, migration, and invasion in GC, similar to the effects of ACK1 overexpression. Silencing of ECD completely blocked the augmentation of ACK1 overexpression‐induced EMT, migration, and invasion. Mechanistically, ACK1 phosphorylated AKT at Thr 308 and Ser 473 and activated the AKT pathway to up‐regulate the transcription factor POU2F1, which directly bound to the promoter region of its novel target gene ECD and thus regulated ECD expression in GC cells. Furthermore, the phosphorylation levels of AKT at Thr 308 and Ser 473 and POU2F1 and ECD levels were positively associated with ACK1 levels in clinical GC specimens. Collectively, we have demonstrated that ACK1 promotes EMT, migration, and invasion by activating AKT–POU2F1–ECD signalling in GC cells. ACK1 may be employed as a new prognostic factor and therapeutic target for GC. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.